Pengaruh Latihan Kelincahan Terhadap Kemampuan Tendangan Sabit Atlit Pencak Silat Dikapasita Desa Teluk Jaya Kecamatan Kelekar - Dwindi Rusdiani; Ferry Hidayad; Puput Sekar Sari (Pusat Riset dan Inovasi Nasional, 2024)
The problem with this research is that there is still a lack of agility This is owned by a pencak silat athlete in Dikapasita, Teluk Jaya Village, Kelekar Distric visible during the match because it is easy for attacks to be caught and read by against. Especially during the sickle kick. The aim of this research is to looking at the effect of agility training on sickle kicking ability. This research is a quasi-experiment, by providing training treatment agility to improve the athlete's sickle kicking ability, with the population 25 athletes, consisting of 20 male athletes and 5 female athletes, sampling technique purposive sampling, with samples taken from 20 male athletes. Instruments in this study was a test of sickle kick ability. Next is data analysis uses the t test to determine the effect. Research result shows 25.25 > 1.73, which means there is an influence between agility training on the sickle kicking ability of Dicapasita pencak silat athletes in Teluk Jaya Village Kelekar District.